2010
DOI: 10.4103/0301-4738.62650
|View full text |Cite
|
Sign up to set email alerts
|

Residual triamcinolone acetonide at macular hole after vitreous surgery

Abstract: Post traumatic macular holes have shown successful anatomic outcomes with vitrectomy with internal limiting membrane (ILM) peeling and gas injection. Intraocular use of triamcinolone acetonide (TA) crystals is gaining popularity in patients for visualization of the vitreous cortex, posterior vitreous detachment induction and ILM peeling during macular hole surgery. However, the possibility of residual steroid crystals clogging the hole at the conclusion of surgery exists. In our case, residual TA was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…noted the presence of triamcinolone particles plugging a traumatic MH and inferred that it possibly delayed hole closure. [ 9 ] On the contrary, we believe that TA may have actually aided the hole closure in their case as it did in our case.…”
Section: Discussioncontrasting
confidence: 45%
“…noted the presence of triamcinolone particles plugging a traumatic MH and inferred that it possibly delayed hole closure. [ 9 ] On the contrary, we believe that TA may have actually aided the hole closure in their case as it did in our case.…”
Section: Discussioncontrasting
confidence: 45%
“…However, we did not find any significant difference in hole closure between the two dyes. Other reports have also shown that residual TA in MHS does not seem to interfere with anatomic or visual improvement [49,50].…”
Section: Discussionmentioning
confidence: 96%
“…TA can accumulate at the edges of MH or straddle the hole edges and hence inhibit closure by mechanical blocking the physiological interactions between the sensory retina and the retinal pigment epithelium (RPE). [ 5 ] There are reports asserting the benefits of the macular plug with TA in persistent MH helping in the closure. [ 6 ]…”
mentioning
confidence: 99%